2020
DOI: 10.1371/journal.pone.0237357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fermented feeds and ginseng polysaccharides on the intestinal morphology and microbiota composition of Xuefeng black-bone chicken

Abstract: Fermented feeds contain abundant organic acids, amino acids, and small peptides, which improve the nutritional status as well as the morphology and microbiota composition of the intestine. Ginseng polysaccharides exhibit several biological activities and contribute to improving intestinal development. Here, Xuefeng black-bone chickens were fed a basal diet fermented by Bacillus subtilis, Saccharomyces cerevisiae, Lactobacillus plantarum, and Enterococcus faecium, with or without ginseng polysaccharides. The 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…VH, CD, and VH/CD are crucial in the intestinal health of animals, which are directly related to the absorption capacity of intestinal mucosa. Studies have reported that morphological changes of the small intestine, such as increasing VH and decreasing CD, enhanced gut digestion and absorption [60,61], which was also found in the current study. Our results showed that FF increased VH of each intestinal segment, decreased jejunal CD, and increased the VH/CD ratio.…”
Section: Discussionsupporting
confidence: 89%
“…VH, CD, and VH/CD are crucial in the intestinal health of animals, which are directly related to the absorption capacity of intestinal mucosa. Studies have reported that morphological changes of the small intestine, such as increasing VH and decreasing CD, enhanced gut digestion and absorption [60,61], which was also found in the current study. Our results showed that FF increased VH of each intestinal segment, decreased jejunal CD, and increased the VH/CD ratio.…”
Section: Discussionsupporting
confidence: 89%
“…Sutterella was reported to produce acetic acid by fermenting incubation (Gao et al, 2018), it was widely prevalent in the human gastrointestinal tract. Its deficiency might alter the colonic microbiota to disrupt the normal function of the colonic epithelium and induce inflammatory bowel disease (Xie et al, 2020). Sutterella could be used as a potential probiotic capable of improving the growth rate and the feed conversion ratio of chickens (Biasato et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Xuefeng black-bone chicken is a famous native breed in the Hunan province of China, which favoured by people due to its high nutritional value. However, there are still problems in the Xuefeng black-bone chicken industry, such as long feeding periods and low laying rate which need some measure to solve Xie et al 2020). Previous studies revealed that Pal or Pro can mitigate the adverse effects of mycotoxins on production performance, and change intestinal morphology and barrier function of animals (Cheng et al 2018;Sli_ zewska et al 2019;Wu et al 2019).…”
Section: Discussionmentioning
confidence: 99%